A. 3(J + 15) = J - 1
B. J + 15 = 3J - 1
C. J + 15 = 3(J - 1)
If J represents John's age, then J + 15 = 3(J - 1) equations could be used to solve the problem
Two or more expressions with an equal sign is called as Equation.
Given that
"I am 3 times as old as Sue is," Frank said to Ann. "On the other hand, I am 15 years older than John while Sue is 1 year younger than John.
F=Frank
J=John
S=Sue.
I am 15 years older than John
In the sense Frankes age is 15 more than John age, So it is 15+J
Sue is 1 year younger than John.
So Sue's age is less than john
J-1
"I am 3 times as old as Sue is"
Three times of J-1
3(J-1)
So equating this we get
Frank's age is equal to three times Sue's age of John minus one, which is the left-hand side of our equation.
15+J=3(J-1)
Hence 15+J=3(J-1) is the equation could be used to solve the problem.
To learn more on Equations click:
#SPJ5
Frank = F
Sue = S
John = J
F=3*S
F = J+15
S = J-1
If you want to find Frank's age, then his age would be equivalent to John's plus 15 years.
A.-Would not work because Frank is three times Sue's age, not John's (left hand side of the equation).
B.-Notice that the right hand side of the equation is equivalent to Sue's age, which we know is John-1, however it is currently written to be "three times Sue's age minus one" which would give us John's age, plus two more years than his actual age on the left hand side.
C.-Frank's age is equal to John's plus fifteen (right side of the equation) and Frank is equal to Sue's age times 3. But, if Sue is in terms of Johns, then Sue's age is John's minus one. Therefore, Frank's age is equal to three times Sue's age of John minus one, which is the left-hand side of our equation.
Therefore C is the answer. C:
O $0.82
O $0.05
O $0.77
Answer:
.82
Step-by-step explanation:
45.75 x .018=.82